HEURISTIC POTENTIAL OF GENERAL POPULATION CENSUSES IN HISTORICAL DEMOGRAPHY (City: History, Culture, Society, 2026)
The article analyzes the heuristic potential of general population censuses as a key source for historical demography, using All-Imperial Population Census of the Russian Empire in 1897 as a case study. It examines the role of censuses in the formation of demography as a scientific discipline and their importance for state governance from the early modern period to the twentieth century. Particular attention is paid to the census program, methodology, publication of results, and the structure of its statistical tables.The study explores the informative value of the 1897 census for investigating population size, social structure, urbanization, migration patterns, levels of education, linguistic and confessional composition, occupational structure, and socio-economic transformations in Dnieper Ukraine at the end of the nineteenth century. Special emphasis is placed on methodological challenges in using census materials, including difficulties in reconstructing ethnic composition due to the absence of ethnic self-identification in the census program, the specific recording of native language and religion, and changes in administrative and territorial boundaries. The article concludes that despite the ideological limitations of the census program, the 1897 census remains one of the most reliable and informative sources for the study of historical demography, socio-economic history, and modernization processes. Its heuristic potential has not yet been exhausted and can be further expanded through critical analysis, recalculation of data, and interdisciplinary approaches.
Keywords: historical demography; population censuses; 1897 census; Russian Empire; Dnieper Ukraine; urbanization; migration; social structure; modernisation